The Impact of Tourism Special Economic Zones (SEZs) in Encouraging Regional Economic Growth - Oktaviana, Nurdiana Kholida; Qibthiyyah, Riatu Mariatul (Jurnal Ekonomi Kuantitatif Terapan; Vol 18 No 1 (2025): Vol. 18, No. 1, FEBRUARI 2025 (pp.1-149)DO - 10.24843/JEKT.2025.v18.i01.P03, 2025)
This paper analyzes the impact of Tourism SEZs in encouraging regional economic growth as measured through GDP. Indonesia has advantages in terms of economy and geography, this advantage makes Indonesia have tourism potential in each region. However, there is a gap in infrastructure and supporting facilities, so the Government of Indonesia through the RPJMN established a Tourism SEZ through collaboration with private companies to encourage economic growth in the area. In addition, this program is expected to measure the impact of Tourism SEZs on regional economic growth and how the gap between regions is. This study uses the Difference in Difference method with Staggered Treatment Timing, with a time period of 2010-2022. The results of the estimate found that the Tourism SEZ did not have a positive and significant influence on regional economic growth. The impact on regional economic growth will only be seen in the long term. In addition, control variables such as population and regional expenditure showed a positive influence, while population density variables had a negative influence on regional economic growth. Keywords : Tourism SEZ; GDP; Diffrence in Difference (DiD) JEL Classification : O18, L83, L88